Managerial Attitudes Toward Industrial Relations : A U.S.-Canadian Comparison - Thompson, Mark; Moore, Larry (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
This paper analyses possible differences in managerial attitudes toward unionism and collective bargaining in Canada and the United States. Divergent patterns of attitudes emerge that are consistent with other observable differences between Canadian and U.S. industrial relations.